Evaluasi Kesesuaian Perhitungan Cadangan Secara Manual Terhadap Penggalian Nyata Bijih Timah Blok Realisasi Pada BWD Kundur 1 PT Timah Tbk Di Laut Penganak Bangka Barat - 0DI RIPANDA; E.P.S.B TAMAN TONO; Alfitri Rosita (Jurusan Teknik Pertambangan Universitas Bangka Belitung, 2019)
BWD Kundur 1 with the ability to dig up to 60 meters below sea level . Tin Mining Processes in theSea Penganak is mined using Bucket Wheel Dredge in the realization block with a total production of30 tons in September 2018. With the production target the calculation of company reserves is greaterthan the production realization of the BWD. The problem obtained in the field is a mismatch of reservecalculations with the realization of extracting tin ore that exceeds the tolerance limit. For good yieldcoefficients, namely 1 - 1.2, which has been set SOP. The reserve calculation uses the manualmethod using the Area of Influence method which this calculation is done by making a polygon area ofthe influence of the borehole and calculating the area of influence of the drill hole manually with 3 drillholes in the realization block of Kundur 1 BWD of 34,348 tons and the results of the realization of the2018 septber month were 30 tons. After obtaining the results of the two reserve calculations and theresults of the realization, then the two results can be compared to determine the Results Coefficient,find the factors that caused the incompatibility of the calculation of the performance such as BWDperformance, the type of layer extracted BWD, weather at the time of excavation and efforts toimprove Results Coefficients such as doing selective mining to determine the productive direction ofmultiplication. From the results of the manual calculation of the realization block obtained Pdh 34,3tons while the results of realization in the Psb field of 30 tons, the percentage difference in the ratio is -12,65% and the Results Coefficient of 0.85 including inappropriate from KH 1.2 according to SOP with0.2 tolerance.